Level of fisherman satisfaction with harbormaster services at Belawan Ocean Fishing Port, North Sumatra Province - Sijabat, Ramayanda Kartini; Brown, Arthur; Zain, Jonny (South East Asian Marine Sciences Journal, 2024)
Service can cause users a sense of satisfaction or dissatisfaction with the performance. This study aims to determine fishermen's satisfaction level with martyrdom services at the Belawan Ocean fishing port, North Sumatra Province. The method used is a survey method by collecting primary and secondary data. The results showed that the level of satisfaction of users of martyrdom services based on the Customer Satisfaction Index method was 72.564 (satisfied). The importance and Performance Analysis method shows that service speed, certainty of service schedules, and suitability of requirements are considered less satisfying for service users. At the same time, service officer responsibility and security characteristics are considered very satisfying for service users